An In Vitro Usage of Origanum majorana Watery Extract as Inhibitory Antibacterial Component against Different Medically Important Bacterial Isolates - Zainab Adil Ghani Chabuck (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Origanum majorana demonstrates a broad spectrum of effectiveness against various diseases, exerting antimicrobial effects against different pathogenic microorganisms. The goals of this research are to provide light on how Origanum majorana extract inhibits human pathogenic bacteria, how it may prevent biofilm development, and how it affects bacterial adhesion. The antibacterial activity of the water-based Origanum majorana extract was assessed in this research using two different methodologies. "Antibiotics were compared to its effectiveness using an agar-well diffusion assay and disc diffusion method," the first step. Additionally, the extract's ability to inhibit biofilm formation and bacterial adherence was assessed through specialized tests. All bacterial isolates of Gram negative, Gram-positive bacterial types were sensitive to Origanum majorana extract and the range of inhibition zone (30 to 24) mm. Although floxacin was effective against some of these isolates, the majority of them were resistant. Most bacterial Gram negative types were exhibit moderate adherence and biofilm activity to this extracts and some bacterial isolated of bacteria were exhibit high adherence and biofilm activity to the watery extracts of Origanum majorana. This research confirms previous findings that Origanum majorana extracts are very effective against a wide variety of clinical isolates of bacteria, including Gram-negative as well as Gram-positive varieties. Notably, the extracts were found to be more effective than commercially available antibiotics. Furthermore, the extracts displayed significant inhibition of bacterial adherence and biofilm formation. Based on these findings, Origanum majorana extracts have great promise as an effective antibacterial and anti-biofilm agent.